Differenzialdiagnostik von Veränderungen in Intraokularlinsen = Differential diagnosis of changes in intraocular lenses - Yildirim, Timur Mert; Auffarth, Gerd U.; Henningsen, Nikola; Łabuz, Grzegorz; Augustin, Victor A.; Son, Hyeck Soo; Mackenbrock, Lars; Khoramnia, Ramin (Klinische Monatsblätter für Augenheilkunde, 2023)
Differentiating between various intraocular lens (IOL) changes can be a challenge. In particular, certain IOL models carry the risk of late postoperative calcification. A major cause of IOL exchange surgery could be avoided if appropriate modifications were made during the IOL manufacturing process. The use of a hydrophilic acrylate carries the risk of IOL calcification, especially when a secondary procedure, such as a pars plana vitrectomy or other procedures using gas or air, is performed. In secondary IOL calcification, there is a wide range of opacification patterns, which are usually located in the centre on the anterior surface of the IOL or sometimes elsewhere. Often, granular deposits accumulate just below or on the surface of the IOL, leading to significant deterioration in visual quality and eventually requiring IOL exchange surgery. Therefore, in the case of eyes requiring secondary surgical intraocular intervention in the future, the use of hydrophilic IOLs should be critically evaluated. With regard to hydrophobic IOL materials, there are clear differences in the susceptibility to the formation of glistenings. Over time, there has been a significant decrease in glistening formation over the past 30 years due to optimisation of the material. With hydrophobic IOLs, special care should also be taken to avoid mechanical damage. In general, the only treatment option for functionally-impairing IOL opacification is surgical lens exchange, which carries potential risks of complications. In cases with a low degree of functional impairment, and especially in eyes with additional ocular diseases, it may be difficult to weigh the risk of additional surgery against the potential benefit. In some cases, it may be more appropriate not to perform an IOL exchange despite the IOL opacification. Recent visualisation methods that allow high-resolution analysis of the opacities in vivo and in vitro may be used in the future to estimate the functional effects of various IOL material changes on the optical quality.
Gesehen am 13.09.2023
Artikel online veröffentlicht: 11. August 2023